Eksplorasi Tumbuhan Obat Tradisional Desa Blata Tatin Kecamatan Kangae Kabupaten Sikka - Helena Lanur; Oktavius Yoseph Tuta Mago (Saintek Lahan Kering, 2018)
The research was distributed by the rampant use of synthetic drugs in treating various diseases, the minimal use of traditional medicine and the lack of data on traditional medicinal plants. The purpose of this research is to explore the medicinal plants in the village of Kangae Tatin, Blata, Sikka. Samples of medicinal plants are collected by exploration survey techniques after obtaining information by interviewing key informants and respondents in the village. The data information of medicinal plants is presented in the form of tabulated and described comprehensively. Results of the study found 13 species of medicinal plants used in the village of Blata Tatin i.e. sambiloto (Andrographis paniculata), bananas (Musa sp.), Hibiscus tiliaceus L., sweet potato (Ipomoea batatas), candlenut (Aleurites moluccana L.), turmeric (Curcuma domestica Val.), Kaempferia galanga L., ginger (Zingiber officinale Rosc.), coconut (Cocos nucifera), Paederia scandens Merr, Centella asiatica L., Piper betle L. and spinach (Amaranthus spinosus L.).